MANIFESTATION OF EMOTIONAL BURNOUT IN THE PROFESSIONAL ACTIVITY OF TEACHERS (Multidisciplinary Journal of Science and Technology, 2026)
This article explores emotional burnout in educators’ professional activity based on an empirical study of preschool and general secondary school teachers. The Maslach Burnout Inventory (MBI), developed by K. Maslach and S. Jackson and adapted by N.E. Vodopyanova, was applied. The results revealed differences in psycho-emotional exhaustion, depersonalization, and reduced personal accomplishment depending on the type of institution. Emotional exhaustion was higher among secondary school teachers, while depersonalization was more pronounced among preschool educators. Both groups showed high levels of reduced personal accomplishment, linked to decreased intrinsic motivation and limited professional growth opportunities. The findings emphasize the need to address socio-psychological factors of burnout and implement preventive measures in educational settings.